H-Bonding and intramolecular catalysis of proton exchange affect the CEST properties of EuIII complexes with HP-DO3A-like ligands. Issue 26 (3rd March 2021) - Baroni, Simona; Carnovale, Irene Maria; Carrera, Carla; Boccalon, Mariangela; Guidolin, Nicol; Demitri, Nicola; Lattuada, Luciano; Tedoldi, Fabio; Baranyai, Zsolt; Aime, Silvio
Abstract : CEST effects depend on the intramolecular proton exchange. Abstract : Eu(HP-DO3A) is present in solution as a mixture of two diastereoisomers whose alcoholic groups are the source of the mobile protons for the CEST effect. The exchange is base catalyzed. Two novel Eu III complexes of HP-DO3A-like ligands containing an amino or a carboxylate functionality in the proximity of the –OH groups showed the occurrence of intramolecular catalysis of the prototropic exchange. New insights into the role of the intramolecular proton exchange on the CEST properties have been gained.